Telehealth Technologies for Heart Failure Disease Management in Rural Areas:An Integrative Research Review - Barbara Ann Graves; Cassandra Ford; Kathryn Davis Mooney (Rural Nurse Organization; Binghamton University, 2013)
Purpose: The purpose of this integrative research review (IRR) is to present evidence of the use and effectiveness of telehealth technologies for improving health outcomes in heart failure (HF) disease management in general as well as the use and effectiveness specific to rural populations. Background: HF is the most common chronic disease cause of hospitalization in the U.S. with subsequent high admission rates and cost. Because many rural areas are designated as medically underserved, disease management for patients with HF living in rural areas is challenging and in need of innovative management strategies. Telehealth technologies have capabilities to provide frequent surveillance and improve outcomes in a variety of health conditions. Methods: An IRR methodology was used to present evidence of the use and effectiveness of telehealth technologies in the provision of disease management to HF patients in both the general and rural populations. Findings: Results showed five broad themes of effectiveness: improved knowledge, improved self-care behaviors, improved health outcomes, cost reduction and patient satisfaction. Telehealth technologies have proven effective in the management of HF patients by detecting changes in health status earlier, decreasing the rates of hospital readmission and emergency department visits, decreasing costs, and improving self-care behaviors and quality of care. Conclusion: Evidence from clinical trials supports the use of telehealth in disease management in general as well as future development of strategies for management of HF in rural populations. Key Words: heart failure, telehealth, rural